Management of patients with recurrent/metastatic endometrial cancer: Consensus recommendations from an expert panel from Brazil - de Andrade, Diocésio Alves Pinto; Guimarães, Andréa Paiva Gadelha; de Melo, Andréia Cristina; Nogueira-Rodrigues, Angélica; Gomes, Larissa Müller; Scaranti, Mariana; Maia, Joyce Maria Lisboa; Morelle, Alessandra Menezes; Santos, Candice Amorim de Araújo Lima; Souza, Cristiano de Pádua; de Freitas, Daniela; Callegaro Filho, Donato; et al. (Frontiers in Oncology, 2023)
Background: Endometrial cancer is of increasing concern in several countries, including Brazil, in part because of an ageing population, declines in fertility, and the increasing prevalence of obesity. Although endometrial tumors had lagged behind other cancer types in terms of treatment improvements, molecular characterization of these tumors is paving the way for novel therapies and an expansion of the therapeutic arsenal. We aimed to help medical oncologists who manage patients with recurrent or metastatic endometrial cancer in the Brazilian healthcare setting. Methods: The panel, composed of 20 medical oncologists, convened in November 2021 to address 50 multiple-choice questions on molecular testing and treatment choices. We classified the level of agreement among panelists as (1) consensus (≥75% choosing the same answer), (2) majority vote (50% to <75%), or (3) less than majority vote (<50%). Results: Consensus was present for 25 of the 50 questions, whereas majority vote was present for an additional 23 questions. Key recommendations include molecular testing for every patient with recurrent/metastatic endometrial cancer; choice of first-line treatment according to microsatellite instability and HER2, with the addition of programmed death ligand 1 (PD-L1) and hormone receptors (HRs) for second-line therapy; carboplatin and paclitaxel as the preferred option in first-line treatment of HER2-negative disease, with the addition of trastuzumab in HER2-positive disease; pembrolizumab plus lenvatinib as a key option in second line, regardless of HER2, PD-L1 or HRs; and various recommendations regarding treatment choice for patients with distinct comorbidities. Conclusion: Despite the existing gaps in the current literature, the vast majority of issues addressed by the panel provided a level of agreement sufficient to inform clinical practice in Brazil and in other countries with similar healthcare environments.